2001
DOI: 10.1080/02652030010021404
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ethnic foods for microbial quality and content aflatoxin

Abstract: A range of ethnic foods was examined for their microbiological content in relation to total viable counts (TVC) of aerobic bacteria, counts of presumptive coliforms, yeast and mould counts; presence of Salmonella spp., Listeria monocytogenes, Escherichia coli O157:H7 and Campylobacter spp.; total enumeration of Clostridium perfringens, Staphylococcus aureus and Bacillus spp.; identification of moulds and the presence of total aflatoxins. Samples, which included cereals, nuts, dried fruits, herbs and spices, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 7 publications
1
37
0
4
Order By: Relevance
“…Dessas, uma apresentava o mesmo tipo de contaminação na superfície (1cm 2 ). Verificou-se, quando da aquisição das amostras, que o funcionário do estabelecimento não cumpria algumas das regras desejáveis de manipulação de alimentos, o que se enquadra na idéia genericamente aceita de que a presença desse microrganismo nos alimentos está, muitas vezes, relacionada com deficientes operações de manipulação (Inghan et al, 2000;Candlish et al, 2001).…”
Section: Resultsunclassified
“…Dessas, uma apresentava o mesmo tipo de contaminação na superfície (1cm 2 ). Verificou-se, quando da aquisição das amostras, que o funcionário do estabelecimento não cumpria algumas das regras desejáveis de manipulação de alimentos, o que se enquadra na idéia genericamente aceita de que a presença desse microrganismo nos alimentos está, muitas vezes, relacionada com deficientes operações de manipulação (Inghan et al, 2000;Candlish et al, 2001).…”
Section: Resultsunclassified
“…Field and storage fungal contaminants of grains in Nigeria had previously been reported by Makun et al, (2007) and in rice in India by Reddy et al, (2004 (Candlish et al, 2001;Rasooli and Abyaneh, 2004).…”
Section: Toxigenic Fungi and Mycotoxinmentioning
confidence: 99%
“…Studies have reported contamination of herbal products with disease causing organisms such as Bacillus sp., Enterobacteriaceae, Salmonella sp., Staphylococcus aureus (Govender et al, 2006). Additionally, elevated levels of coliforms and soil born bacteria contaminants have been observed in herbal drugs and spices (Candlish et al, 2001). The other challenge is the presence of "adulterants" which in actual sense mean intentional or unintentional presence of undeclared ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal herbs have been reported to be contaminated with microorganisms indigenous to the soil and plants where they are grown (Okunlola et al, 2007;Govender et al, 2006;Czech et al, 2001). Poor conditions during harvesting and post-harvest handling of the herbs and herbal products also predispose them to contamination (Farkas, 2000;Candlish et al, 2001). Studies have reported contamination of herbal products with disease causing organisms such as Bacillus sp., Enterobacteriaceae, Salmonella sp., Staphylococcus aureus (Govender et al, 2006).…”
Section: Introductionmentioning
confidence: 99%